Fabrication of cu2o based homostructure thin films using electrodeposition method - Mohamad Arifi, Nurliyana (2018)
Copper oxide (Cu2O) is one of inorganic materials used in photovoltaic (PV) technology. It was reported that Cu2O that acts as the p-n junction semiconductor material was preferable in extensive studies for solar cell application. However, the heterojunction interface between p-type Cu2O to other materials has lower conversion efficiency due to lattice mismatch. Thus, a p-n Cu2O homojunction thin film had been introduced to acquire higher efficiency due to similar interface which can promote less defects between layers. In this experiment, both n and p-type Cu2O thin film was fabricated by using copper acetate based solution through electrodeposition method. Firstly, the effects of pH value and deposition time were optimized for fabrication of n-type Cu2O thin film on fluorine doped thin oxide (FTO) glass. The deposition potential optimization was conducted using Cyclic Voltammetry Measurement. Then, the effects of bath temperature and deposition time were optimized for p-type Cu2O on n-type Cu2O/FTO substrate to obtain p-type based homostructure. Structural, morphological, topological and optical properties were characterized by using Cyclic Voltammetry, X-ray diffraction (XRD), Field Emission-Scanning Electron Microscope (FE-SEM), Atomic Force Microscopy (AFM) and Ultraviolet-Visible Absorption Spectroscopy (UV-Vis), respectively. The conduction type for n-type and p-type Cu2O thin film also have been characterized by using Photoelectrochemical Measurement (PEC). The optimum parameters obtained for n-type Cu2O were pH of 6.3, deposition time of 30 minutes, bath temperature of 60 °C and deposition potential of -0.125V vs Ag/AgCl. Meanwhile, the optimum parameters for fabrication of p-type Cu2O on n-type Cu2O/FTO susbstrate were pH of 12.5, deposition time of 2 hours, bath temperature of 40 °C and potential deposition of -0.4 V vs Ag/ AgCl. The p-type Cu2O based homostructure thin film was successfully fabricated and can be implemented in fabrication of Cu2O homojunction thin film in photovoltaic for solar cell.